Walbridge, J. (2014). The Alexandrian Epitomes of Galen. vol.1 A parallel English-Arabic text translated, introduced, and annotated. Utah, Brigham Young University Press - Brito, Rodrigo Pinto de (Revista Archai, 2016)
Review: Walbridge, J. (2014). The Alexandrian Epitomes of Galen vol. 1: On the Medical Sects for Beginners; The Small art of Medicine; On the Elements According to the Opinion of Hippocrates. A parallel English-Arabic text translated, introduced, and annotated by john Walbridge. Utah: Brigham Young University Press, 2014